The Value of African American Poetry in Community Settings - Jenkins, Treasure Ann (My University, 2016)
This research study presents the perspectives of nine residents of Duluth, MN and Superior, WI (the "Twin Ports"), upon the reading of African American poetry. The study attempts to assess the importance of exposure to African American poetry and the significance of interacting with the published work. The hope is to move toward an appreciation of African American artistry, for the purpose of more equitable relationships across racial divides. Keeping the rich literary expression of African American stories and experiences alive nurtures the spirit, giving shape to the past and foundation to the future. The study seeks to examine the potential for enrichment, through reading African American poetry in community settings, for people in and around the Twin Ports area.
Keywords: Fine and Applied Arts; Superior, Wisconsin; Twin Ports; Communicating Arts; Duluth, Minnesota; Community; Dominant White culture; African American culture; African American poetry; Storytelling